2019
DOI: 10.1021/acs.jnatprod.9b00697
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents from the Aerial Parts of Agastache rugosa and Their Inhibitory Activities on Prostaglandin E2 Production in Lipopolysaccharide-Treated RAW 264.7 Macrophages

Abstract: A new flavone glucoside, acacetin-7-O-(3″-O-acetyl-6″-O-malonyl)-β-d-glucopyranoside (1), two new phenolic glucosides, (3R,7R)-tuberonic acid-12-O-[6′-O-(E)-feruloyl]-β-d-glucopyranoside (14) and salicylic acid-2-O-[6′-O-(E)-feruloyl]-β-d-glucopyranoside (15), and two new phenylpropanoid glucosides, chavicol-1-O-(6′-O-methylmalonyl)-β-d-glucopyranoside (17) and chavicol-1-O-(6′-O-acetyl)-β-d-glucopyranoside­(18), as well as 26 known compounds, 2–13, 16, and 19–31, were isolated from the aerial parts of Agastac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Rosmarinic acid and five acacetin derivates were detected in 70% ethanolic extract of A. rugosa by using HPLC (Figure 2), and 14 flavonoids, including acacetin, diosmetin, and luteolin, were isolated in our laboratory previously [9]. The compounds identified in A. rugosa in this study are similar to those identified in previous studies and those deposited in ingredient databases.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Rosmarinic acid and five acacetin derivates were detected in 70% ethanolic extract of A. rugosa by using HPLC (Figure 2), and 14 flavonoids, including acacetin, diosmetin, and luteolin, were isolated in our laboratory previously [9]. The compounds identified in A. rugosa in this study are similar to those identified in previous studies and those deposited in ingredient databases.…”
Section: Discussionsupporting
confidence: 86%
“…The chemical components in A. rugosa were searched for using public databases in TM-MC: A database of medicinal materials and chemical compounds in Northeast Asian traditional medicine (http: //informatics.kiom.re.kr/compound/, updated 3 December 2018) and Korean Traditional Knowledge Portal (http://www.koreantk.com/ktkp2014/, updated 14 December 2019) [24]. Information of chemical components isolated previously from A. rugosa in our laboratory was also used for the study [9]. Through the above process, a total of 99 components derived from A. rugosa were identified (Supplementary Table S1).…”
Section: Searching Chemical Components In a Rugosamentioning
confidence: 99%
“…To clarify the biological properties of WEAR and the mechanisms underlying its benefits, we next investigated the phytochemical profile of WEAR. A. rugosa has been reported to contain essential oils and several types of compounds, such as phenylpropanoids, lignans, flavonoids, and terpenoids [ 7 , 8 ]. The typical UV (at 280 nm) base peak chromatograms and the extracted ion chromatogram for each WEAR analyte are shown in Figure 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen reference standards with more than 98% were used to identify the phytochemicals in WEAR. Chlorogenic acid and neochlorogenic acid were purchased from ChemFace (Wuhan, China), and rosmarinic acid, citrusin C, nepetoidin B, diosmetin-7- O-β - d -glucopyranoside, tilianin, isoagastachoside, acacetin, apigetrin, phlorizin, luteolin, diosmetin, apigenin, acacetin-7- O -(6″- O -malonyl)-β- d -glucopyranoside, acacetin-7- O -(3″- O -acetyl)-β- d -glucopyranoside, and acacetin-7- O -(2″- O -acetyl-6″- O -malonyl)-β- d -glucopyranoside were isolated from A. rugosa as previously described [ 7 ]. The Dionex UltiMate 3000 system equipped with a Thermo Q-Exactive mass spectrometer (Thermo Fisher Scientific, San Jose, CA, USA) was used as in previously described methods [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation